INNOVATIVE PSYCHOLOGICAL STRATEGIES FOR DEVELOPING STUDENTS' EMOTIONAL INTELLIGENCE AND PROVIDING MENTAL HEALTH IN THE PROCESS OF TRAINING HIGHLY QUALIFIED PERSONNEL IN THE CONTEXT OF GLOBALIZATION. (Universal International Scientific Journal, 2026)
This study is devoted to the study of innovative psychological strategies for developing students' emotional intelligence and ensuring mental health in the context of accelerating globalization processes. In the modern education system, not only the formation of professional knowledge and skills, but also the development of a person's emotional stability, stress resistance and social adaptability are of great importance. In this regard, students' emotional intelligence is considered one of the important psychological factors ensuring personal and professional success. The study analyzes the structural components of emotional intelligence, its impact on students' mental health and professional readiness from a theoretical and practical perspective. Also, new socio-psychological requirements arising in the context of globalization, academic workload, competitive environment and increasing information flow are studied as factors affecting students' mental health.
Keywords: emotional intelligence, students, mental health, globalization process, innovative psychological strategies, stress resistance, social adaptability, higher education system, training of highly qualified personnel, psychological stability.